2009
DOI: 10.1001/archgenpsychiatry.2009.17
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mediotemporal and Ventrostriatal Function in Humans by Δ9-Tetrahydrocannabinol

Abstract: The modulation of mediotemporal and ventrostriatal function by Delta9-THC may underlie the effects of C. sativa on verbal learning and psychotic symptoms, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
132
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(140 citation statements)
references
References 47 publications
4
132
0
Order By: Relevance
“…Oral CBD (300-600 mg) alone has been reported to produce mild sedative and anxiolytic effects in some studies (Zuardi et al, 1993;Crippa et al, 2004Crippa et al, , 2011Bergamaschi et al, 2011a, b), whereas most report no measurable psychoactivity (Benowitz et al, 1980;Borgwardt et al, 2008;Bhattacharyya et al, 2009;Winton-Brown et al, 2011;see Niesink and van Laar, 2013). When combined with THC, some have shown that (1) smoked CBD (150 μg/kg) attenuated the 'euphoric' effects of smoked THC (25 μg/kg; Dalton et al, 1976) and (2) oral CBD (1 mg/kg) reduced spontaneous reports of oral THC intoxication (Zuardi et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Oral CBD (300-600 mg) alone has been reported to produce mild sedative and anxiolytic effects in some studies (Zuardi et al, 1993;Crippa et al, 2004Crippa et al, , 2011Bergamaschi et al, 2011a, b), whereas most report no measurable psychoactivity (Benowitz et al, 1980;Borgwardt et al, 2008;Bhattacharyya et al, 2009;Winton-Brown et al, 2011;see Niesink and van Laar, 2013). When combined with THC, some have shown that (1) smoked CBD (150 μg/kg) attenuated the 'euphoric' effects of smoked THC (25 μg/kg; Dalton et al, 1976) and (2) oral CBD (1 mg/kg) reduced spontaneous reports of oral THC intoxication (Zuardi et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…While the precise neuroanatomical regions responsible for CBD's actions are not known, considerable evidence implicates the nucleus accumbens (NAc) as an important site for CBD's modulatory effects on various cognitive and behavioral phenomena (Guimarães et al, 2004;Bhattacharyya et al, 2009;Valvassori et al, 2011;Mijangos-Moreno et al, 2014;Pedrazzi et al, 2015). For example, CBD attenuates THCinduced dysregulation of the ventral striatum during verbal recall tasks (Bhattacharyya et al, 2009) and increases c-fos and adenosine levels in rodent NAc (Guimarães et al, 2004;Mijangos-Moreno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CBD attenuates THCinduced dysregulation of the ventral striatum during verbal recall tasks (Bhattacharyya et al, 2009) and increases c-fos and adenosine levels in rodent NAc (Guimarães et al, 2004;Mijangos-Moreno et al, 2014). In addition, CBD blocks amphetamine-induced oxidative stress in the NAc (Valvassori et al, 2011) and intra-NAc CBD attenuates amphetamineinduced deficits in prepulse inhibition (Pedrazzi et al, 2015;Renard et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Under experimental conditions, a single dose of its main psychoactive ingredient, delta-9-tetrahydrocannabinol (THC), can result in the acute induction of transient psychotic symptoms in man similar to that seen under the influence of cannabis, and these acute effects have been linked to its effects on prefrontal, medial temporal and striatal function (Bhattacharyya et al, 2009;D'Souza et al, 2008D'Souza et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%